2015
DOI: 10.1016/j.atmosres.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Global modeling of the nitrate radical (NO3) for present and pre-industrial scenarios

Abstract: Increasing the complexity of the chemistry scheme in the global chemistry transport model STOCHEM to STOCHEM-CRI (Utembe et al., 2010) leads to an increase in NO x as well as ozone resulting in higher NO 3 production over forested regions and regions impacted by anthropogenic emission. Peak NO 3 is located over the continents near NO x emission sources. NO 3 is formed in the main by the reaction of NO 2 with O 3 , and the significant losses of NO 3 are due to the photolysis and the reactions with NO and VOCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 90 publications
3
37
0
Order By: Relevance
“…1. NO 3 experiences a very large change between PI and PD (up to more than 1000 % in the Northern Hemisphere), which is also seen in other model studies that show good agreement between modeled presentday concentrations of NO 3 and observations (Khan et al, 2015). The prescribed PI values of surface layer O 3 in the region around Paris used in this study are around a factor of 2 higher than the measured PI values at a station near Paris in the study of Volz and Kley (1988) corresponds with findings from other studies (Parrish et al, 2014).…”
Section: Reaction Reactionsupporting
confidence: 82%
See 2 more Smart Citations
“…1. NO 3 experiences a very large change between PI and PD (up to more than 1000 % in the Northern Hemisphere), which is also seen in other model studies that show good agreement between modeled presentday concentrations of NO 3 and observations (Khan et al, 2015). The prescribed PI values of surface layer O 3 in the region around Paris used in this study are around a factor of 2 higher than the measured PI values at a station near Paris in the study of Volz and Kley (1988) corresponds with findings from other studies (Parrish et al, 2014).…”
Section: Reaction Reactionsupporting
confidence: 82%
“…Lohmann (2017) shows that model estimates of ERF ari+aci (ari is aerosol-radiation interactions and aci is aerosol-cloud interactions) vary from −0.07 to −3.41 W m −2 , while the Fifth Assessment Report (AR5) from the Intergovernmental Panel on Climate Change (IPCC) gives an expert judgement of ERF ari+aci of −0.9 W m −2 , with a 5 to 95 % uncertainty range of −1.9 to −0.1 W m −2 mostly coming from the uncertainties in the aci component (Boucher et al, 2013). Uncertainties in the natural background emissions have been highlighted as a large contributor to the uncertainty in the indirect effects (Lohmann et al, 2000;Kirkevåg et al, 2008;Hoose et al, 2009;Carslaw et al, 2013), while pointed out that its sensitivity to parameterizations of microphysical processes in global models is even higher. In this study, we examine a third factor, namely the oxidants involved in the formation of aerosols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass burning emissions of CH 4 , CO, SO 2 , NO x , and nonmethane VOCs (Table S4) have been scaled by using global scaling factors from the Edgar‐Hyde emissions database [ van Aardenne et al , ]. More details about the preindustrial scenario can be found in Khan et al []. All simulations were run with meteorology from 1998 for a period of 24 months with the initial 12 months being discarded as a spin‐up year.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Two further experiments (referred to as 'B1800' and 'ISOP1800') were performed for a preindustrial scenario described in Khan et al [71]. All simulations were conducted with meteorology from 1998 for a period of 24 months with the first 12 allowing the model to spin up.…”
Section: Model Descriptionmentioning
confidence: 99%